Fornasini-Marchesini 2-D state space models: Transfer function computation via the DFT - Antoniou, George E.; Emmons, Kelly (Zielona Góra: Uniwersytet Zielonogórski)
A new algorithm is presented for the computation of the coefficients of the determinantal polynomial and the coefficients of the adjoint polynomial matrix of a given two-dimensional (2-D) state space model of Fornasini-Marchesini type. The algorithm has been implemented in Matlab and uses the discrete Fourier transform (DFT). The simplicity and efficiency of the technique are illustrated by two examples.
Keywords: two dimensions system theory; Fourier transform; DFT algorithm; Fornasini-Marchesini's model